Knowledge, attitude, and practices of parents on the importance of their Children's oral health in Greater Noida, India - Sukhdeep Singh; Neha Awasthi; Dhirja Goel; Deepak Khandelwal; Priyanka Sachdeva; Rakshana Bakhtawar (Wolters Kluwer Medknow Publications, 2021)
Background: Parents and family members are considered the primary source for knowledge about child rearing and health habits for children. Young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs, which affect oral hygiene and healthy eating habits. Parental perception has a long-term influence in determining a child's oral health status. Aim: The aim of this study is to assess the oral health-related knowledge, attitude, and practices (KAP) of parents with children aged 3-5 years. Materials and Methods: A total of 500 parents of children aged 3 to 5 years were included in the study. A self-administered questionnaire, written both in English and local language (Hindi), validated through pre-tested survey, was given to the parents to assess the oral health related KAP. The results were calculated on the basis of frequency and percentages using the SPSS software. Results: Males comprised 49.8% and females comprised 50.2% of the respondents of questionnaire. Majority of fathers and mothers of the study population agreed for the importance of primary teeth. Almost all the participants in this study agreed that a child's teeth should be brushed/cleaned. A little less than half of study population considered 1 year as the suitable age for the child's first dental visit. A higher proportion of females as compared to males felt that night time bottle/breastfeeding leads to caries. Conclusion: Parental attitude, knowledge, and practices are responsible for their child's oral health. No statistical significance was seen between mothers and fathers on perception of their child's oral health care.